Towarzystwa muzyczne w Królestwie Polskim (1870–1914) - Jaworski, Wojciech (Acta Universitatis Lodziensis. Folia Historica, 2015)
In the years 1870–1914 in the Polish Kingdom was established in at least 38 associations, whose aim was to promote the music alone or with choral singing, and 2 trade unisons of musicians. During of the repression after January Uprising and reactionary rule of emperor Alexander III (to 1894) was legalized only 3 organizations, regulation social life (1894–1906) – 12, and liberalization (1906–1914) – 25. Out of province (between the years 1867–1912), the most music associations founded in Piotrków Province (18), which resulted from its potential economic and demographic. In Warsaw Province registered 6 associations, Kalisz – 4, Łomża and Lublin – 3. In terms of the type locality, 17 organizations established in provincial cities, 13 in country towns, 4 in other towns, and 2 in the villages. Most of them set up at 6 in Łódź and Warsaw, 2 in Lublin, Radom and Siedlce. In view of the attempt to create an organization for Jewish state authorities pursue policies limiting. In terms of socio-professional among the founders initially dominated by the townspeople sometimes supported by landed aristocracy. After the outbreak of the revolution in 1905, activity began to manifest petty, officials and workers. The creation of musical societies contributed mainly Poles, to a lesser extent Germans, Russians, French, Ukrainians and Jews.